BS EN IEC 62148-21. Fibre optic active components and devices. Package and interface standards. Part 21. Design guide of electrical interface of PIC packages using silicon fine-pitch ball grid array (S-FBGA) and silicon fine-pitch land grid array (S-FLGA) (10th April 2020) - British Standards Institution,
No abstract available